Survey of population and threats of a cites listed butterfly Troides aeacus aeacus (Felder and Felder, 1860) in central Nepal - Khanal, Bhaiya (Journal of Natural History Museum, 2022)
The population of Troides aeacus aeacus is declining due to habitat threats in many parts of central Nepal. The population survey was done by direct observation with a random walk in the morning sun from 8 a.m. to 12 p.m., considering its appropriate months of appearance. There was no issue with counting repetition since this species appeared in single or double individuals at each locality of this survey. This work, which covered an elevation range of 550 to 2000 m, was carried out in central Nepal between May and July of 2017 and April, May, and September of 2018. A total count of 56 individuals of this butterfly was recorded in this survey, which covered adjoining districts like Bhaktapur, Lalitpur, Kathmandu, Makwanpur, and Nuwakot. The observed small population and distribution gaps of this butterfly in a few locations were primarily caused by habitat loss, the absence of sufficient plants that provide nectar for adults and food for larvae, and tourism activity, which was particularly noticeable in Nagarkot (Bhaktapur) and Chitlang (Makwanpur). In addition, the impact was seen primarily as a result of road construction, forest fires, and small landslides in some of its habitat areas in Makwanpur and Chandragiri.